A population‐based study of the incidence of delusional infestation in Olmsted County, Minnesota, 1976–20103. (May 2014) - Bailey, C.H.; Andersen, L.K.; Lowe, G.C.; Pittelkow, M.R.; Bostwick, J.M.; Davis, M.D.P.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Population‐based studies of the incidence of delusional infestation (DI), a disorder with dermatological and psychological components, have not been performed. What does this study add? While still rare, DI is more common than previously estimated. The annual incidence was 1·9 (95% confidence interval 1·5–2·4) per 100 000 person‐years. Mean age at diagnosis was 61·4 years (range 9–92), and incidence increased with age and time.